Pengaruh CAR, NPL, LDR Terhadap Profitabilitas Bank (ROA) Tahun 2017-2019 - Pricilla Febryanti Widyastuti; Nur Aini (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
The purpose of this research is to analyze and test the effect of CAR, NPL, LDR on bank profitability (ROA). The population in this study were all banking companies listed on the Indonesia Stock Exchange (IDX) during 2017 - 2019 which amounted to 128 companies. The sampling method used in this research is using the census technique, that is, all companies can be used as samples or can be said to be full samples. The data analysis method used in this research is multiple linear regression analysis. The results of this study reveal that CAR and LDR have no effect on bank profitability (ROA), while NPL has a significant negative effect on bank profitability (ROA).